36.3k views
0 votes
(z^2 - 3z) (z + 1) ​

User ShahiM
by
5.4k points

2 Answers

1 vote

Answer:

Today : Saturday, 07 November 2020

Hour: 20.04 WIB (Indonesia)

_______________________________

(z² - 3z) (z + 1)

= z³ + z² - 3z² - 3z

= z³ - 2z² - 3z

User Termosa
by
5.2k points
2 votes

Answer:

z³ - 2z² - 3z

Explanation:

(z² - 3z)(z+1) = (z²*z) + (z²*1) + (-3z*z) + (-3z*1) = z³ + z² - 3z² - 3z

= z³ -2z² - 3z

User Gilad Gat
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.